APPLICATION OF THE METHOD OF LIBERATION FROM CONNECTIONS TO PARTICULAR STATEMENTS OF PROBLEMS - Makhmudova, Ш.Д.; Makhmudov, А.Д.; Urazgalieva, А. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
Dynamic systems leading to optimal control problems occurring as a function of time are of significant interest. Studies of various processes in complex systems, including information systems, are characterized by the conflict nature of decision-making or conditions of uncertainty. Real systems can be considered as complex systems: in economics these are enterprises and industries, in social life these are various teams, groups, communities. Game theory is widely used in the study of complex systems. Under conditions of uncertainty, the decision-making “player” only has information about the set of possible strategies (situations) that he can adopt and the quantitative measure of “winning” that he can receive when choosing the situation in which he is currently located. This article complements and gives a more complete understanding of the method of freeing from connections using the example of some problem statements. In particular, a study of differential games with phase constraints will be carried out.